Severe Hypothyroxinemia in a Young Adult with Carbimazole-Treated T3-Predominant Graves’ Hyperthyroidism, Reversed with L-Thyroxine Loading Immediately Post-Total Thyroidectomy - Chiang, Brenda; Kon, Yin Chian (Journal of the ASEAN Federation of Endocrine Societies, 2021)
Patients with triiodothyronine (T3)-predominant Graves’ hyperthyroidism with markedly elevated serum thyroid stimulating immunoglobulin (TSI) levels and massive goitre may display discordant hypothyroxinemia with eutriiodothyroninemia or hypertriiodothyroninemia while on anti-thyroid drug therapy. A 25-year-old female with the above was started on oral carbimazole therapy for 9 months before total thyroidectomy. Preoperatively, her serum free T4 was reduced to below detection limit, and total T4 reduced to 11% of lower limit of normal, while T3 levels remained normal, and TSH remained largely suppressed. Immediately after total-thyroidectomy, a loading dose of L-thyroxine (L-T4) was administered intravenously. She was extubated without any postoperative complications. Serum free and total T4, and TSH normalized within the next 24 hours. The peculiar thyroid axis dynamics and use of L-T4 postoperative loading in such a rare clinical scenario are discussed.